Exploring the Relationship between Organizational Culture, Organizational Commitment and Performance in Commercial Banks in Two African Countries - Naidoo, S.; Govender, Krishna K. (International Review of Management and Marketing, 2022)
Although the relationship between organizational culture, organizational commitment and organizational performance has been thoroughly researched in most developed countries, not much research has been conducted in developing countries, especially in Africa. Thus, being sparked by the erratic performance, an on-line survey was conducted among to reflect the above relationships. With respect to organizational employees from a commercial bank in two African countries, to test 12 (twelve) hypotheses which were postulated commitment, the study focused on the three antecedents, namely, normative, affective and continuance commitment, rather than the composite concept. Upon analysis of the data from a non-probability sample of 265 respondents using structural equation modelling, it was ascertained that there is no relationship between the three antecedents of organizational commitment and the performance of employees in both the combined, as well as in the individual bank samples. However, although no relationship existed between organizational culture and employee performance, a strong positive relationship was ascertained between organizational culture and organizational performance. Considering that the findings do not necessarily concur with much of what has been reported in the literature, the implications of the findings on the performance of the sampled banks as well as for future research, are discussed.